Effect of the abiotic factors on brachymetra albinervis albinervis (Heteroptera: Gerridae) - Giehl, Nubia França da Silva; Fonseca, Paula V B; Dias-Silva, Karina; Brasil, Leandro Schlemmer; Cabette, Helena Soares Ramos (Iheringia - Serie Zoologia, 2015)
We analyzed the influence of abiotic factors, longitudinal and temporal distribution on the abundance of Brachymetra albinervis albinervis Amyot & Serville, 1843. Three sites of Cerrado stream were assessed: headwater, intermediary and river mouth, monthly for a year (June 2011 to May 2012). At each site, the following abiotic variables were monthly measured in a linear 100 meters transect: dissolved oxygen, water temperature, pH, electrical conductivity, width and depth of the stream. Were collected 111 specimens. The river mouth presented lower abundance when compared with others sites (F(2,9) = 13.721, p = 0.001). The periods of the year (rain, ebb, dry or early rains), there was no differences in the abundance. Thus, the abundance of B. a. albinervis analyzed for one year showed variation only in the streams longitudinal distribution, which was attributed to the effect of environmental changes in the river mouth, where presented lower abundance and less environmental integrity. These results contribute to the ecological knowledge of this species and discusses the change in the occurrence and abundance this species due to alteration in aquatic environments. © 2015, Fundacao Zoobotanica do Rio Grande do Sul. All rights reserved.
Efeito de fatores abióticos sobre Brachymetra albinervis albinervis (Heteroptera: Gerridae)